2021
DOI: 10.1590/1413-81232021262.07062019
|View full text |Cite
|
Sign up to set email alerts
|

Coocorrência de fatores de risco à saúde em universitários de uma instituição de ensino superior brasileira

Abstract: Resumo A coocorrência de fatores de risco pode desencadear doenças crônicas não transmissíveis e no extremo, a mortalidade. Os objetivos deste estudo foram descrever as prevalências e analisar as características sociodemográficas e de vínculo com a universidade associadas à coocorrência de fatores de risco em universitários. O estudo, composto por três inquéritos transversais, foi realizado com universitários da Bahia, Brasil, nos anos de 2010, 2012 e 2014. O desfecho foi a coocorrência de dois ou mais fatores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
1
3
1
2
Order By: Relevance
“…Students in the pre-clinical phase of medical education and in the 18-20 years age bracket presented with higher total Fantastic lifestyle scores when compared with students in later phases of medical education and in older age brackets. This corroborates previous data that state that as students age and progress further into higher-education, lifestyles have a propensity towards being augmented with risky behaviors [ 31 , 32 ]. Thus, the pre-clinical phase of medical education may present itself as a promising moment for lifestyle interventions focused on preventing such decline, but it is important to focus on interventions other than only formal education, as it alone appears to be ineffective in preventing worsening lifestyle behaviors over the course of time [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…Students in the pre-clinical phase of medical education and in the 18-20 years age bracket presented with higher total Fantastic lifestyle scores when compared with students in later phases of medical education and in older age brackets. This corroborates previous data that state that as students age and progress further into higher-education, lifestyles have a propensity towards being augmented with risky behaviors [ 31 , 32 ]. Thus, the pre-clinical phase of medical education may present itself as a promising moment for lifestyle interventions focused on preventing such decline, but it is important to focus on interventions other than only formal education, as it alone appears to be ineffective in preventing worsening lifestyle behaviors over the course of time [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, the analysis of the sample power of this study demonstrates that between the categories of one and two risk behaviors there is an inadequately sample size to confirm such an association. Although this study did not find associations between one and two risk behaviors, in other studies these risk behaviors isolated 2,15 or combined into two variables 20,39,40 were described as health risk characteristics, which influence a negative SRH. Thus, it is suggested that the co-occurrence of two risk behaviors in health promotion at the university should not be disregarded, with a view to improving SRH.…”
Section: Discussioncontrasting
confidence: 65%
“…Evidence shows that the prevalence of simultaneous exposure to health risk behaviors increases with age, 9,46 since young people acquire greater autonomy and economic independence with advancing age. 9 However, this association has not been well established in the literature.…”
Section: Discussionmentioning
confidence: 99%